Analytical fragility analysis of southern Illinois wall pier supported highway bridges. - Bignell, John (Earthquake engineering & structural dynamics.)
An analytical fragility analysis was conducted in order to characterize the seismic vulnerability of existing southern Illinois wall pier supported highway bridges to potential earthquakes. To perform this fragility analysis, a detailed inventory survey was first taken of the wall pier bridges identified in an earlier random sampling of southern Illinois priority emergency route bridges. From the survey three types of wall pier bridges were identified. Of those identified, hammerhead and regular wall pier supported bridges represented nearly 90% of the population. Incorporating structural variations determined from the random sample survey, nearly 100 three-dimensional nonlinear finite element models were constructed. Each model was subjected to a randomly assigned synthetic earthquake representative of those that could potentially occur within the region. From these analyses, a series of wall pier supported bridge fragility curves were produced. In addition, a liquefaction fragility analysis was conducted in order to characterize the seismic vulnerability of southern Illinois wall pier supported highway bridge sites to liquefaction in potential earthquakes. To perform this second fragility analysis, wall pier bridges within the southern Illinois random sample that may be susceptible to liquefaction were identified. A soil profile from each of these susceptible bridge sites was then subjected to randomly assigned bedrock motions, and an Arias intensity liquefaction analysis was carried out. From these analyses, a fragility curve for the potentially liquefiable wall pier supported bridge sites was produced. Overall results of this study indicate that southern Illinois wall pier supported bridges are moderately vulnerable to structural damage in a 2% probability of exceedance in 50 year earthquake, and in some cases they could also be highly vulnerable to on-site liquefaction events.